2013
DOI: 10.1371/journal.pone.0085307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel QTLs for Isolate-Specific Partial Resistance to Plasmodiophora brassicae in Brassica rapa

Abstract: Plasmodiophora brassicae, the causal agent of clubroot disease of the Brassica crops, is widespread in the world. Quantitative trait loci (QTLs) for partial resistance to 4 different isolates of P. brassicae (Pb2, Pb4, Pb7, and Pb10) were investigated using a BC1F1 population from a cross between two subspecies of Brassica rapa, i.e. Chinese cabbage inbred line C59-1 as a susceptible recurrent parent and turnip inbred line ECD04 as a resistant donor parent. The BC1F2 families were assessed for resistance under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 53 publications
2
95
0
Order By: Relevance
“…napus through homeologous recombination between A, C and R genomes is eminently possible. Several cytological studies have shown high frequency of homologous chromosome pairing among C subgenomes of Brassica species [14, 30, 38]. Our results showed that the C subgenomes in Brassicoraphanus (RRCC, 2n = 36) and B .…”
Section: Discussionsupporting
confidence: 57%
“…napus through homeologous recombination between A, C and R genomes is eminently possible. Several cytological studies have shown high frequency of homologous chromosome pairing among C subgenomes of Brassica species [14, 30, 38]. Our results showed that the C subgenomes in Brassicoraphanus (RRCC, 2n = 36) and B .…”
Section: Discussionsupporting
confidence: 57%
“…(), Chen et al . () and Zhang et al . () to be linked with Crr1 gene, were not associated with resistance to any of the pathotypes.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, the resistance gene in the DH population used in this study (derived from ECD 04), when screened against the old Canadian P. brassicae pathotypes 2, 3, 5, 6 and 8, was traced to the same genomic region where CRa and/or CRb Kato are found (Zhang et al, 2015a). In contrast, the resistance gene in ECD 04-derived populations mapped to the A08 chromosome when screened against Chinese P. brassicae pathotypes (mainly pathotype 4); this is a region where the Crr1 gene has been reported (Chen et al, 2013;Zhang et al, 2015b). Similarly, two major QTLs on the A03 and A08 chromosomes were found to confer resistance to multiple German (four), Swedish (two) and French (one) P. brassicae field and single-spore isolates in an ECD 04-derived DH population (Werner et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations